1977
DOI: 10.3758/bf03335325
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on thirst: Cutaneous or oral receptors?

Abstract: Water intake of rats was not greatly different as a function of the ambient temperature in which the water was consumed provided that the temperature of the water was maintained at 25°C. If water temperature was allowed to follow ambient temperature, then less water was consumed in cool environments. Thirst is modulated by receptors in or around the mouth and not in the skin.It is well-known that water intake varies directly with ambient temperature (Budgell, 1970;Hamilton, 1963), presumably as a consequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Early rodent-based research showed that saliva production was increased in rats with cold (0 °C) versus warm (22 and 37 °C) beverage ingestion (Pangborn, Chrisp, & Bertolero, 1970). Furthermore, fluid consumption in rats was not different when ambient (skin) temperature was cold (5 °C) or warm (40 °C), but when both mouth and skin temperature were altered together, cold-fluid consumption was reduced (Carlisle, 1977). These findings were interpreted as evidence for an orolingualreceptor mechanism that influences fluid consumption by feedback from temperature-sensitive receptors in the mouth rather than skin.…”
Section: Discussionmentioning
confidence: 99%
“…Early rodent-based research showed that saliva production was increased in rats with cold (0 °C) versus warm (22 and 37 °C) beverage ingestion (Pangborn, Chrisp, & Bertolero, 1970). Furthermore, fluid consumption in rats was not different when ambient (skin) temperature was cold (5 °C) or warm (40 °C), but when both mouth and skin temperature were altered together, cold-fluid consumption was reduced (Carlisle, 1977). These findings were interpreted as evidence for an orolingualreceptor mechanism that influences fluid consumption by feedback from temperature-sensitive receptors in the mouth rather than skin.…”
Section: Discussionmentioning
confidence: 99%
“…The association between drink temperature and drinking behavior has been reported extensively. Water temperature appears to have an immediate satiating effect on thirst, which suggests the involvement of an orolingual receptor mechanism (Carlisle, ). Taken together with previous studies (Pangborn et al., ; Boulze et al., ; Brunstrom & Macrae, ), Brunstrom () suggested that the ingestion of cold water is (a) likely to be labeled as “thirst‐quenching;” (b) likely to be chosen and ingested in greater quantities when individuals are thirsty; and (c) is most sensitive to hedonic shifts caused by mouth dryness.…”
Section: Rationale For Investigating Drink Temperaturementioning
confidence: 99%